Magnesium recovery from brines using exopolymeric substances of sulfate-reducing bacteria. Issue 53 (13th November 2016) - Wan, Abdul-Matiin; Mansoor, Bilal; Ahmad, Farrukh
Abstract: Magnesium recovery from brines was studied ex situ under sulfate-reducing conditions and in the presence of active cells and exopolymeric substances (EPS) using an innovative experimental approach. EPS was extracted and a mixed sulfate-reducing inoculum was enriched from dolomitizing coastal microbial mats. The inoculum tested positive for the presence of the Desulfovibrio brasiliensis, the organism associated with biogenic dolomitization, using denaturing gradient gel electrophoresis. Cultures were incubated within dialysis tubes, together with TEM grids that provided an imaging-ready substratum for biofilm growth and mineral precipitation. The anaerobic incubations lasted 16 d under a continually increasing bulk solution magnesium ion concentration. The following reactor configurations were incubated: (A) bacteria-only, (B) bacteria + pre-extracted EPS, (C) pre-extracted EPS-only, and (D) control. The TEM grids were recovered for analysis using spot, line transect, and areal SEM–energy-dispersive X-ray analysis for elemental comparison of deposits. Pre-extracted EPS-bearing cultures, both with and without bacterial inoculum, induced surface-associated magnesium recovery in 16 d. Overall, magnesium recovery in the EPS-only system was 2.2 x (line transect) to 1.5 x (areal) greater than the bacteria + EPS system, while the bacteria-only ( de novo EPS only) and control (no EPS) reactors displayed no surface-associated magnesium recovery. Analysis of microstructures within the bacteria + pre-extracted EPS system revealed variations in the Mg:Ca ratios, ranging from 19.9 to 61.9% (spot analysis) over different deposit morphologies, suggesting a dynamic biologically mediated mineralization process for magnesium recovery from brines requiring further investigation.